The most patient man: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This tale recounts the life of a man who exemplifies extraordinary patience in the face of trials and tribulations. It teaches children about resilience and the rewards of maintaining faith during difficult times.